Frequency of emotional disturbances among hostelites and day scholars medical students - Shireen Jawed; Benash Altaf; Rana Muhammad Tahir Salam; Farhat Ijaz (Journal of the Pakistan Medical Association, 2020)
Abstract Objectives: This study was aimed to determine and compare the frequency of the emotional disturbances, anxiety and depression among the medical students on Hospital Anxiety Depression scale (HAD) score among the hostelites and day scholars. Methodology: This cross sectional study was conducted at private medical college in Faisalabad, Pakistan, from March 2019 to April 2019, comprising of 105 male and female students. Validated Hospital Anxiety depression scale (HAD-A and HAD-D) was used to collect data from 1st year and 2nd year MBBS students in order to evaluate anxiety and depression among them. Data was analyzed on SPSS 21. Pearson’s Chi-square was applied to compare the percentages of anxious and depressed subjects among the studied group. Independent sample t-test was applied for comparison of mean HAD scores between hostelites and day scholars. P value ? 0.05 was taken as significant. Results: There were 105 students in the study with a mean age of 19.4± 0.68 years. Overall, 82.7% students had anxiety, and 52.1% suffered from depression. Average HAD –A and HAD- D scores were 11.2 ± 3.41 and 7.2 ± 3.37 respectively. Greater number of hostelites was suffering from emotional disturbances as compared to day scholars. HAD –A scores was significantly higher in hostelites than day scholars with P value 0.003*(11.85 ± 3.42 Vs 10.92 ±2.56). HAD- D scores were also higher in hostilities but difference was insignificant. (7.57± 3.42 Vs 6.85 ±1.58) Continuous...